PEMBELAJARAN KEBENCANAAN BAGI MASYARAKAT DI DAERAH RAWAN BENCANA BANJIR DAS BERINGIN KOTA SEMARANG - Edi Kurniawan, Erni Suharini, Dewi Liesnoor S dan Edi K Dewi Liesnoor S (Faculty of Social Science, Universitas Negeri Semarang, 2015)
The high level of flood risk that occurs in Semarang city, raises the level of anxiety in the community , so it needs to have integration in community disaster education . The purpose of this paper is to inform the public profile of the flood prone areas in the form of non-spatial data base ( behavior towards disaster , habits and aspirations of the community in the face of disaster), and a disaster for developing learning models in shaping the character of the community . While the methods used are qualitative and Research and Development ( RnD ) The results showed that there is still a lack of knowledge in the society faces a disaster , it is shown by the lack of social and physical infrastructure of flood disaster . On the other hand to increase the capacity of communities to deal with disasters , disaster on the community learning can be done with the participation of the community ranging from mitigation , preparedness , disaster response , to recovery .Lessons of disaster is one of the strategies in the character building , because learning through disaster also internalized values ? ? of at least three characters , namely social care , care for the environment , and creative . Social care is realized by mutual cooperation , caring environment with hygiene and environmental conservation activities , and creative embodied through effective post-disaster management .